Relevansi Pemikiran Ekonomi Islam di Indonesia Menurut Imam Al- Maqrizi di Era Kontemporer - Faradila Az Zahra; Lina Marlina Susana (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2026)
Classical Islamic economic thought has made significant contributions to addressing modern economic issues, one of which is the ideas of Imam Al-Maqrizi, who is known for his criticism of unfair economic practices. This study aims to examine the relevance of Imam Al-Maqrizi's Islamic economic thought in the contemporary Indonesian context. The focus of the study is his views on inflation, economic crises, monetary instability, wealth hoarding, and the role of the state in maintaining economic justice and social welfare. This study uses a library research method with a qualitative-descriptive approach, through an analysis of Al-Maqrizi's works and contemporary Islamic economic literature relevant to the Indonesian economy. The results indicate that Al-Maqrizi's thought has strong relevance to current Indonesian economic problems, such as inflation due to unstable monetary policy, speculative practices, unequal distribution of wealth, and weak state oversight of the market. The Islamic economic values ​​proposed by Al-Maqrizi, such as justice, welfare, moral control of economic actors, and state responsibility, can serve as a normative and practical basis for formulating contextual Islamic economic policies. Thus, Imam Al-Maqrizi's Islamic economic thought is not only historical but also relevant and applicable in strengthening Indonesia's economic system, which is just and oriented towards the welfare of the people in the contemporary era. Abstrak Pemikiran ekonomi Islam klasik memiliki kontribusi penting dalam merespons persoalan ekonomi modern, salah satunya melalui gagasan Imam Al-Maqrizi yang dikenal kritis terhadap praktik ekonomi yang tidak berkeadilan. Penelitian ini bertujuan untuk mengkaji relevansi pemikiran ekonomi Islam Imam Al-Maqrizi dalam konteks Indonesia di era kontemporer. Fokus kajian diarahkan pada pandangannya mengenai inflasi, krisis ekonomi, ketidakstabilan moneter, penimbunan harta, serta peran negara dalam menjaga keadilan ekonomi dan kesejahteraan masyarakat. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan pendekatan kualitatif-deskriptif, melalui analisis terhadap karya-karya Al-Maqrizi dan literatur ekonomi Islam kontemporer yang relevan dengan kondisi perekonomian Indonesia. Hasil kajian menunjukkan bahwa pemikiran Al-Maqrizi memiliki relevansi yang kuat dengan problem ekonomi Indonesia saat ini, seperti inflasi akibat kebijakan moneter yang tidak stabil, praktik spekulasi, distribusi kekayaan yang timpang, serta lemahnya pengawasan negara terhadap pasar. Nilai-nilai ekonomi Islam yang ditawarkan Al-Maqrizi, seperti keadilan, kemaslahatan, pengendalian moral pelaku ekonomi, dan tanggung jawab negara, dapat dijadikan landasan normatif dan praktis dalam merumuskan kebijakan ekonomi Islam yang kontekstual. Dengan demikian, pemikiran ekonomi Islam Imam Al-Maqrizi tidak hanya bersifat historis, tetapi juga aktual dan aplikatif dalam memperkuat sistem ekonomi Indonesia yang berkeadilan dan berorientasi pada kesejahteraan umat di era kontemporer.